MOTIVASI SANTRI MASUK KE PONDOK PESANTREN DAR EL HIKMAH KELURAHAN SIMPANG BARU KECAMATAN TAMPAN PEKANBARU PROVINSI RIAU - Ningsih, Sri Ayu; Maemunaty, Titi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The formulation of the problem in this study is which is the most dominant between intrinsic and extrinsic motivation which causes students to enter Dar El Hikmah Islamic boarding school, Simpang Baru Village, Tampan District, Pekanbaru, Riau Province? The purpose of this study was to determine the most dominant between intrinsic and extrinsic motivations that led to students entering the Dar El Hikmah Islamic Boarding School, Simpang Baru Village, Tampan District, Pekanbaru, Riau Province. This research is descriptive with a quantitative approach. The population in this study were 564 people. Sampling in this study using purposive sampling technique. The data research instrument was a questionnaire with 73 statements of Weight for each answer for Very True (SB) with a score of 4, True (B) with a score of 3, Quite True (CB) with a score of 2, Not True (KB) with a score of 1. Results From the research findings on 2 (two) indicators it can be concluded that these indicators are classified as High Enough. Evidenced by the recapitulation presentation of the percentage of motivation to enter Dar El Hikmah Islamic Boarding School, the overall indicators are: (1) Intrinsic Motivation with a percentage of 63%, (2) Extrinsic Motivation with a percentage of 52%. The meaning is that the motivation of the students to enter the Dar El Hikmah Islamic Boarding School, Simpang Baru Village, Tampan District, Pekanbaru, Riau Province, is quite high.Key words: Students' motivation, Islamic boarding school